Proteinase Activated Receptors Mediate the Trypsin-Induced Ca2 + Signaling in Human Uterine Epithelial Cells - Shmygol, Anatoliy; Brosens, Jan J. (Frontiers in Cell and Developmental Biology, 2021)
Embryo implantation is a complex and tightly regulated process. In humans, uterine luminal epithelium functions as a biosensor gauging the embryo quality and transmitting this information to the underlying endometrial stromal cells. This quality control ensures that only high quality embryos are implanted, while aberrant ones are rejected. The mechanisms of the embryo-uterine mucosa crosstalk remain incompletely understood. Trypsin, a serine protease secreted by the blastocyst, has been implicated in the cross-signaling. Here we address the mechanisms by which trypsin triggers the intracellular calcium signaling in uterine epithelium. We found that protease-activated G-protein coupled receptors are the main mechanism mediating the effects of trypsin in human uterine epithelium. In addition, trypsin activates the epithelial sodium channels thus increasing the intracellular Na+ concentration and promoting Ca2+ entry on the reverse mode of the sodium/calcium exchanger.